The Florence Nightingale Effect: Organizational Identification Explains the Peculiar Link Between Others’ Suffering and Workplace Functioning in the Homelessness Sector - Ferris, Laura J.; Jetten, Jolanda; Johnstone, Melissa; Girdham, Elise; Parsell, Cameron; Walter, Zoe C. (Frontiers in Psychology, 2016)
Frontline employees in the helping professions often perform their duties against a difficult backdrop, including a complex client base and ongoing themes of crisis, suffering, and distress. These factors combine to create an environment in which workers are vulnerable to workplace stress and burnout. The present study tested two models to understand how frontline workers in the homelessness sector deal with the suffering of their clients. First, we examined whether relationships between suffering and workplace functioning (job satisfaction and burnout) would be mediated by organizational identification. Second, we examined whether emotional distance from clients (i.e. infrahumanization, measured as reduced attribution of secondary emotions) would predict improved workplace functioning (less burnout and greater job satisfaction), particularly when client contact is high. The study involved a mixed-methods design comprising interview (N = 26) and cross-sectional survey data (N = 60) with a sample of frontline staff working in the homelessness sector. Participants were asked to rate the level of client suffering and attribute emotions in a hypothetical client task, and to complete questionnaire measures of burnout, job satisfaction, and organizational identification. We found no relationships between secondary emotion attribution and burnout or satisfaction. Instead, we found that perceiving higher client suffering was linked with higher job satisfaction and lower burnout. Mediation analyses revealed a mediating role for identification, such that recognizing suffering predicted greater identification with the organization, which fully mediated the relationship between suffering and job satisfaction, and also between suffering and burnout. Qualitative analysis of interview data also resonated with this conceptualization. We introduce this novel finding as the ‘Florence Nightingale effect’. With this sample drawn from the homelessness sector, we provide preliminary evidence for the proposition that recognizing others’ suffering may serve to increase job satisfaction and reduce burnout – by galvanizing organizational identification.